Circulating resistin is a significant predictor of mortality independently from cardiovascular comorbidities in elderly, non-diabetic subjects with chronic kidney disease - Marouga, A; Dalamaga, M; Kastania, A.N.; Kroupis, C.; Lagiou, M.; Saounatsou, K.; Dimas, K.; Vlahakos, D.V. (Biomarkers, 2016)
CONTEXT: Resistin is associated with inflammation, atherosclerosis and cardiovascular (CV) disease. OBJECTIVE: To associate circulating resistin with all-cause and CV mortality in chronic kidney disease (CKD) patients. METHODS: Serum resistin was determined in a cohort of 80 elderly, non-diabetic patients with stable CKD at different stages in a follow-up period of 5 years. RESULTS: Circulating resistin was significantly elevated in deceased compared to alive patients. Resistin emerged as an independent biomarker of all-cause and CV mortality after a 5-year follow-up period. CONCLUSION: Elevated circulating resistin was a significant independent predictor of CV and all-cause mortality in elderly, non-diabetic CKD patients
DA - 20160331 IS - 1366-5804 (Electronic) IS - 1354-750X (Linking) LA - eng PT - Journal Article PT - Research Support, Non-U.S. Gov't SB - IM